Dissecting between-plant and within-plant wage dispersion - Evidence from Germany - Daniel Baumgarten; Gabriel Felbermayr; Sybille Lehwald (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2016)
We analyze the most important drivers of the recent rise in overall German wage dispersion and pin down the relative contribution of central establishment and worker characteristics. Moreover, we separately investigate the drivers of between as well as withinestablishment wage dispersion. Using rich linked employer-employee data for the Germanmanufacturing sector between 1996 and 2010, we explicitly account for the role of a plant'scollective bargaining regime, its technological status and its export behavior. In order todisentangle the contribution of each single variable to the rise in wage dispersion, relativeto other variables, requires a rich and comprehensive framework. To this end we apply astate-of-the-art decomposition method which is based on recentered influence function (RIF)regressions. We find that the decline in collective bargaining coverage as well as changesin the skill- and occupation-related wage structure are main sources of increased overallwage dispersion. Regional employment shifts, differences between collectively covered anduncovered plants and increased sorting play a key role for changes in between establishmentwage dispersion, while the technology intenstiy of a plant is the most important driver ofwithin plant wage inequality
Keywords: J31; F16; 330; Wage inequality; Decomposition; RIF-Regression; Linked employeremployee data